Rukun Kematian Dalam Pertukaran dan Sanksi (Studi Kasus di Desa Hadungdung, Kecamatan Portibi, Kabupaten Padang Lawas Utara) - Wahyuni, Sri; Yusuf, Yusmar (Journal of Education Religion Humanities and Multidiciplinary, 2024)
The pillar of death is a community tradition in Hadungdung Village which is carried out to ease the burden on families who are experiencing misfortune due to the death of one of their family members. The pillar of death is not just a cultural tradition but in the pillar of death there is a high value of solidarity between communities. Exchange and sanctions in the pillar of death are one of the forms of practice carried out in the pillar of death in Hadungdung village. The formulation of the problem in this study is what is the meaning of the pillar of death in the community of Hadungdung village, how the exchange is practiced in the pillar of death in Hadungdung village and how sanctions are practiced on members of the pillar of death in Hadungdung village. The informants of this study amounted to 6 (six) people, namely the chairman of the death pillar and members of the death pillar, in determining the research informants, the researcher used the purposive technique. Data collection was carried out using observation, interview and documentation methods. The results of the study show that the pillar of death for the people of Hadungdung village as a form of help, the exchange system carried out in the pillar of death is not just in the form of labor and material assistance, people who come to condole and help will get a packet of rice and side dishes as a sign of gratitude. Clear and firm sanctions in the pillar of death make the members of the pillar of death more responsible and obedient to the applicable rules.